Business Transformation Towards Sustainability: The Role of Green Accounting in Sustainability Management - Soraya, Bunga; Nurrochmah, Aliatus; Hwihanus, Hwihanus (Indonesian Journal Publisher, 2024)
Green accounting, as an accounting approach that integrates environmental and social factors into a company's financial reporting system, plays an important role in supporting business transformation towards sustainability. This article aims to explore the role of green accounting in sustainability management and how its application can assist companies in managing and reporting their sustainability performance effectively. Through a review of literature and previous research, it is found that green accounting enables companies to identify, measure and disclose the environmental impacts of their business activities more comprehensively. The integration of green accounting in sustainability management also allows companies to develop more comprehensive sustainability performance indicators, set targets, and monitor progress in achieving their sustainability goals. The implementation of green accounting can increase corporate transparency and accountability, build trust and a better reputation, and increase the competitiveness and value of the company in the long run. This article concludes that the role of green accounting is crucial in ensuring that companies consider environmental and social impacts in their business decisions, and create long-term value for stakeholders while minimizing negative impacts on the environment and society.